Train Stations Spatial and Technological Challenges in Iraq: A Case Study (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Innovation has two key levers: the capacity to consider and predict consumer desires, on the one hand, and the building of collaboration between the economic environment, metropolitan players, and knowledge and development actors, somewhere else. Innovation is not just technical, and it disrupts traditions and station partners' aspirations and perceptions: planners, administrators, consumers or clients, and causes a change in locations and uses. The expansion of the rail network in Iraq is renewing station sites, especially in Iraq, which, at the cost of medium-sized cities between these cities, prefer the logic of productivity-focused on express services between major cities. On the field, this alternative translates into two styles of stations that are central base stations for significant towns, and medium- and small-town terminals—establishing stations benefits from an interconnected phase of all spatial organization types. Suppose we research the decision phase that led to the establishment of train stations in Iraq. In that case, we find that this option and construction strategies are a mixture of component elements according to the area details served and actors' strategies. Most chosen sites result from deep relationships between global, regional, and local reasoning.